(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
The global landscape of education is undergoing significant transformation, especially in higher education. As nations aim to modernize and adapt to the demands of the 21st century, higher education institutions face immense challenges in evolving to meet the ever-changing needs of students, faculty, industries, and governments. In this context, effective management is crucial to ensuring the success of reforms. This article explores how improving management practices can play a key role in enhancing the transformation process of higher education systems.